Faculty Opinions towards Introducing e-Learning at the University of Bahrain - Jamlan, Muain (International Review of Research in Open and Distributed Learning, 2004)
E-Learning is an important tool for delivery, interaction, and facilitation of both teaching and learning processes. Faculty members at the University of Bahrain’s College of Education are being encouraged to become involved in e-learning activities. To assess faculty opinions on e-learning, a questionnaire was sent to 30 faculty members of the University’s College of Education to determine how they perceive e-learning, and how they might choose to integrate it into their everyday teaching activities. Data was collected and analyzed by using descriptive statistics. Results indicate that faculty generally perceive e-learning as a positive force in helping students’ achieve their learning objectives. Answers to this questionnaire, however, also indicated areas of weakness: specifically that baseline technological and human resource prerequisites are necessary to support e-learning, and that these baseline prerequisites are not yet available at the University of Bahrain. Other baseline prerequisites are: staff training, well prepared online courses and learning materials, sufficient groundwork for the smooth transition from traditional modes of learning towards e-learning delivery, and the implementation of a more robust technological infrastructure to support all the technical aspects necessary to launch and sustain e-learning.